COMPARATIVE EVALUATION OF RETRIEVAL EFFICIENCY IN YAHOO, BING, AND BAIDU: A STUDY ON RELEVANCE AND SEARCH PERFORMANCE - Khan, Mashood Yousuf; Khan, Zahid Yousuf; Akhoon, Irfan ul Haq (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Purpose: This paper aims to evaluate and compare the performance and efficiency of three popular search engines—Yahoo, Bing, and Baidu—in retrieving relevant internet resources. The study focuses on the accuracy and effectiveness of search engines using single and double-word queries with basic search techniques at specific intervals. Design: The study begins with an analysis of existing methodologies for evaluating search engines, aiming to identify key factors for selecting the most efficient search engine for internet research. Retrieval efficiency is assessed based on several parameters, such as search engine coverage and the occurrence of dead, missing, and duplicate links. A total of 20 single and double word queries are employed to test the engines’ performance. MS Excel is used for data analysis and evaluation. Findings: The results indicate that different search engines use distinct technologies to retrieve web information. Overall, Yahoo outperforms Bing and Baidu in retrieval score; however, Bing shows superior efficiency by retrieving fewer dead and duplicate links, particularly in response to two-term queries. Originality/Value: This paper offers valuable insights into the comparative effectiveness of Yahoo, Bing, and Baidu in retrieving relevant web resources. The findings can guide users, researchers, and search engine developers in optimizing their search strategies and enhancing search engine technologies.